PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 1 JUNJUNG SIRIH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low news writing skills of seventh-grade students at SMP Negeri 1 Junjung Sirih. The purpose of this study was to determine the effect of the Problem-Solving learning model on these students' news writing skills. This study used a quantitative, quasi-experimental method using a One Group Pretest-Posttest Design. The sample size for this study was 32 students. Data were collected through news writing tests before (pretest) and after (posttest) the Problem-Solving model was administered. The results showed that the average student writing ability score increased from 62.34 in the pretest (poor category) to 79.62 in the posttest (good category). This average increase was 17.28, and the posttest score exceeded the Minimum Completion Criteria (KKM) of 75. Therefore, it can be concluded that the Problem-Solving learning model has a significant and effective effect on improving students' news writing skills.